The role of welfare systems in affecting out-migration: the case of Central and Eastern Europe - Kureková, L (International Migration Institute, 2011)
This paper analyses the role of welfare systems in shaping migration patterns in Central and Eastern Europe over the transition process and after EU accession. It argues that states have played a crucial role in affecting migration by creating and widening opportunities for potential and actual migrants through welfare system policies. This explains why CEE countries where social spending figures have been lower, unemployment benefit schemes less extensive, and where labour market mismatches remained unaddressed, experienced greater out-migration. Investigating the role of sending states’ institutions in a comparative framework and over time, this paper analyses migration as part of broader social and economic processes and contributes to our understanding of how sending countries’ institutional factors affect out-migration.